2015
DOI: 10.1128/jcm.00970-15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of BD Max StaphSR and BD Max MRSA XT Assays Using ESwab-Collected Specimens

Abstract: The BD Max MRSAXT and the BD Max StaphSR assays were validated for the detection of methicillin-resistant Staphylococcus aureus (MRSA) in ESwab samples. In addition, the BD Max StaphSR assay was evaluated for its ability to detect and differentiate S. aureus and MRSA in the same sample. A total of 255 ESwab samples collected from the anterior nares of patients were tested by each of three BD Max assays, including the BD Max MRSA first-generation assay. The results were compared to those of direct and enrichmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…False-positive detection of MRSA can lead to unnecessary isolation and increased costs. Previous evaluations of the specificity of commercial assays for the molecular detection of MRSA in nasal swabs indicate that most assays exhibit a specificity of Ն95% (22,31,32). The MRSA NxG assay evaluated in this study showed similar performance characteristics, with an overall specificity of 97.2%.…”
Section: Discussionsupporting
confidence: 51%
“…False-positive detection of MRSA can lead to unnecessary isolation and increased costs. Previous evaluations of the specificity of commercial assays for the molecular detection of MRSA in nasal swabs indicate that most assays exhibit a specificity of Ն95% (22,31,32). The MRSA NxG assay evaluated in this study showed similar performance characteristics, with an overall specificity of 97.2%.…”
Section: Discussionsupporting
confidence: 51%
“…Despite the limited reports of mecC in human isolates, a number of commercial S. aureus PCR assays, available in the UK, now include a mecC target (9,14,15). Similarly, various research groups have designed mecC primers for their S. aureus PCR assays, which we also found to be the most appropriate method when selecting a mecC target for our established S. aureus PCR (16)(17)(18).…”
Section: Discussionmentioning
confidence: 91%
“…However, six out of eight isolates in fact carried the mecA gene, which would provide a corrected specificity rate of 99.8%. Other studies performed in the United States and Europe have reported sensitivity and specificity rates of Ն94.3% and Ն97.7%, respectively (29,30). However, it is important to mention that these studies evaluated the performance of the BD Max StaphSR from nasal swab samples or directly from blood specimens.…”
mentioning
confidence: 99%